Numerical analysis of global and local performance variations of proton exchange membrane fuel cell with different bend layouts and flow directions. (15th September 2020) - Zhang, Xian-Wen; Wang, Xue-Jian; Cheng, Xiao-Zhang; Jin, Lei; Zhu, Jian-Wei; Zhou, Tao-Tao
Abstract: In this work, a three-dimensional multi-component transport CFD model is established to discuss the discrepancies of local distributions under channels and ribs based on the serpentine flow field. Globally, increment of activation loss in the gas diffusive layer takes more effects on catalytic activity than decrease of oxygen concentration. Locally, current density under the channels and ribs is more affected by activation loss and oxygen concentration, respectively. Then the performance of four serpentine flow fields with different bend layouts and flow directions were compared according to the mean value and variance of current density and membrane water content on the cathode membrane surface. The results show that the current density on the membrane surface of the serpentine flow field with non-overlapping bends is more uniform and the standard deviation is about 6.25% lower than that of the overlapping bend. Co-flow has some advantages in uniformity of water content distribution on the cathode membrane surface, and the standard deviation is about 12.6% lower than that of the counter-flow. For large-scale and multi-channels serpentine flow field, the serpentine flow field with non-overlapping bends and co-flow has better application than other three types. Highlights: The discrepancies of global and local distributions of serpentine flow field are specifically studied. The performance of four serpentine flow fields with different bend layouts and flow directions were compared. BNO–CO has some advantages in uniformity of current density and water content distribution than other three.